Mineralocorticoid receptor signaling reduces numbers of circulating human naïve T cells and increases their CD62L, CCR7, and CXCR4 expression. Issue 6 (10th April 2014) - Besedovsky, Luciana; Linz, Barbara; Born, Jan; Lange, Tanja
<x xml:space="preserve">Abstract</x> The role of mineralocorticoid receptors (MRs) in human T‐cell migration is not yet understood. We have recently shown that the MR antagonist spironolactone selectively increases the numbers of circulating naïve and central memory T cells during early sleep, which is the time period in the 24 h cycle hallmarked by predominant MR activation. To investigate whether this effect is specific to spironolactone's blockade of MRs and to study the underlying molecular mechanisms, healthy humans were given the selective MR‐agonist fludrocortisone or placebo and numbers of eight T‐cell subsets and their CD62L and CXCR4 expression were analyzed. Fludrocortisone selectively reduced counts of naïve CD4+, central memory CD4+, and naïve CD8+ T cells and increased CXCR4 expression on the naïve subsets. In complementing in vitro studies, fludrocortisone enhanced CXCR4 and CD62L expression, which was counteracted by spironolactone. Incubation of naïve T cells with spironolactone alone reduced CD62L and CCR7 expression. Our results indicate a regulatory influence of MR signaling on human T‐cell migration and suggest a role for endogenous aldosterone in the redistribution of T‐cell subsets to lymph nodes, involving CD62L, CCR7, and CXCR4. Facilitation of T‐cell homing following sleep‐dependent aldosterone release might thus essentially contribute to sleep's well‐known role in supporting adaptive immunity.